Social networks and customer loyalty: review of loyalty keys and main social networks publications’ characteristics - Dávila Espuela, Nélida; Reina Paz, Maria Dolores; Sevilla Sevilla, Claudia (Frontiers in Psychology, 2023)
The aim of this work is to shed light on the characteristics and relationship between customer loyalty and publications by the companies on social networks; it has been undertaken with the aid of an exhaustive review of previous studies from 1994 up to the present time. The purpose of the research is to generate a model that can tackle the practical characteristics of the publications on social networks to encourage loyalty. With a view to this, a model is developed that is an extension of the traditional "Four Stage Loyalty Model" based on other constructions of the same model, and combined with the characteristics of social networks publications defined in earlier literature. This reflexive approach is particularly important here due to the fact that companies have to be closer to customers' requirements and customers have the option to choose from which type of communication they wish to be the object.